(untitled) (Research, Society and Development, 2022)
The research’s is to carry out a search in the literature on the role of nurses in obstetric violence, together with the adoption of possible preventive measures adopted by this professional. The following research corresponds to a descriptive study, with a qualitative methodological approach, using the Integrative Literature Review as a technique together with the PICO strategy to formulate the guiding question. The research was carried out between September and October 2021 in the databases available and indexed within the Virtual Health Library, namely: LILACS, MEDLINE, and BDENF, through the combination of three Health Descriptors, crossed with the operator boolean “AND”: Obstetric Violence AND, Saúde da Mulher AND, Nursing, being found 157 publications in total, after the criteria this number reduced to 51, being selected 10 articles to compose this review. With regard to obstetric violence and care for the prevention of these cases, it is necessary to conceptualize the violence that happens before, during and after childbirth, with special care for these abused women being of paramount importance. Therefore, it is expected that the present research can serve as a subsidy to guide the political and public guidelines that are exercised by the professional nurse in the face of obstetric violence to obtain excellent results regarding the safety of these women.